2013
DOI: 10.2519/jospt.2013.4868
|View full text |Cite
|
Sign up to set email alerts
|

The Working Mechanism of Manual Therapy in Participants With Chronic Tension-Type Headache

Abstract: Chronic tension-type headache (CTTH) is associated with cervical spine impairments, including restricted range of motion (ROM) of the cervical spine, reduced neck flexor endurance, and greater forward head posture. 13,15,17,27,30 These associations have led to the development of a biomechanical model for CTTH. According to this conceptual model, cervical dysfunction elicits headache through peripheral or central pain mechanisms; therefore, improvement of cervical dysfunction by physical treatment should reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…Finally, the time the patient maintained the craniocervical flexion position from T0 to T3 increased markedly (from 3 s to 32 s) to a value very close to those obtained from asymptomatic subjects (38.95 ± 26.4) ( 17 ). According to recent evidence, increased neck flexor endurance is crucial for improving patients with CTTH ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the time the patient maintained the craniocervical flexion position from T0 to T3 increased markedly (from 3 s to 32 s) to a value very close to those obtained from asymptomatic subjects (38.95 ± 26.4) ( 17 ). According to recent evidence, increased neck flexor endurance is crucial for improving patients with CTTH ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the application of strengthening exercises, ergonomic/posture correction programs and motor control exercise programs have demonstrated to be effective in TTH [64][65][66]. Interestingly, Castien et al found that neck flexor musculature endurance partially mediates the potential effects of manual therapy interventions in TTH [67]. Nevertheless, it should be noted that there are several studies also showing the presence of similar musculoskeletal disorders of the cervical musculature, e.g., decreased neck muscle endurance [68], increased activity of the superficial muscles during low-load isometric tasks [69], and altered muscle performance [70] in people suffering from migraine.…”
Section: Scientific Evidence Of Exercise Interventions For Headachesmentioning
confidence: 99%
“… This model was used to analyse potential mediation between the independent variable (Pain Exposure Physical Therapy versus conventional treatment), the mediator variable (fear-avoidance beliefs or pain catastrophizing or kinesiophobia), and the dependent variable (pain-related disability or pain) [ 30 ]. PEPT = Pain Exposure Physical Therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Only if both effects (between-group differences) were statistically significant, using alpha levels of up to 0.10 due to the exploratory nature of this study, we performed the third analysis, in which we regressed the dependent variables on both the mediators and the independent variable. For mediation to be present, the mediator had to be significantly related to the outcome (path b) and the direct effect of the independent variable on the outcome (arrow c 1 ) had to be smaller than the total effect (arrow c) [ 30 ]. On the basis of the standardised coefficients, we also planned to assess the proportion of mediated effect: (c—c 1 )/c x 100% [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation